Bienestar psicológico y su influencia en el rendimiento académico de las estudiantes de sexo femenino de la Universidad Nacional de Loja. Periodo marzo- Julio 2014 - Merino Jiménez, Silvia Leonor (2015)
This research was realized in order to identify the influence of psychological welfare in the academic performance of the students of feminine sex of the National University of Loja; measure the level of general psychological welfare of the population investigated; establish the level of psychological welfare of each of the dimensions proposed by the BIEPS-J scale, being: control of situations, psychosocial links, life projects, self-acceptance; and, determining the average general of qualifications obtained in the cycle March -July 2014. by the characteristics of the research used a methodology, cross-section descriptive analytics, which uses quantitative methods; the investigated sample consists of 400 female students of all areas with their careers, whit a aged between 18 and 24 years; the instruments used are: the Bieps- J. scale, which measures the psychological welfare and the of each student's general average qualifications, allowing to know the academic performance of the people investigated; throwing as results being more frequently to very good; with respect to the dimensions of the above scale it is set first personal projects; in academic performance rating predominates Very Good. these variables allow interpreting that there is influence of psychological well in academic performance, or vice versa; noting that one cannot say which of the two variables affect the second, still important continue with investigations concerning the topic to determine which of the two causal variables is influential in the second. KEY WORDS: Psychological welfare, Dimensions, academic performance